Entre espelho e fantasia: a aventura da modernidade de São Paulo à Ribeirão Preto (1920-1930) - Vicente, Lucas Guimarães [UNESP] (2015)
This work intends to analyze the process of capitalization / modernization through economic Circuit Sao Paulo and as echoed in Singapore in the 1920s This process is fostered via coffee complex, brought a new social temporality to the city. In this context, we note the look of a coffee elite that seeks to become modern and understood the industrialization and modernization as synonyms situations. We seek to highlight the dialogism of modernity / modernization by observing the elite imperatives to modernize, in that it used the power of the spaces of newspapers and almanacs and at the same time, value is interference in the inner city. Thus redefining the collective memory of the city in the construction and representation of an ideal metropolis. If you really analyze this modernity / modernization reaches all spaces or just materialized in diminished scale, the fantasy of modernity of an elite, which was sold in the always-the-same